Microrobots: Laser‐Printing and 3D Optical‐Control of Untethered Microrobots (Advanced Optical Materials 19/2017). Issue 19 (4th October 2017) - Avci, Ebubekir; Grammatikopoulou, Maria; Yang, Guang‐Zhong
Abstract : In article number1700031, Ebubekir Avci, Maria Grammatikopoulou, and Guang‐Zhong Yang report the design, manufacturing, and control of an untethered articulated microrobot under laser light. The two‐photon photopolymerization (2PP) method is used to manufacture the mechanism. Development of a floating multicomponent optical micromechanism is significant because the articulated microrobots have potential to be used in complex biomedical applications where control in 3D space is required.